The lies of Sarah Palin : the untold story behind her relentless quest for power - Dunn, Geoffrey (New York : St. Martin's Press, 2011)
Based on more than two-hundred interviews--many of them with Republican colleagues and one-time political allies of Palin's--and more than forty-thousand pages of uncovered documents, Dunn chronicles Palin's troubling penchant for duplicity in grim detail, from her dysfunctional childhood in Wasilla through her contentious run for mayor and her failed governorship of Alaska. He also provides the shocking inside story of her betrayal of running mate John McCain during the 2008 presidential campaign and her self-serving resignation as governor in July of the following year. Dunn deftly places Palin in the American tradition of right-wing demagogues--from Huey Long to Joe McCarthy--and details her troubling obsession with Barack Obama as it fuels her own political ambitions and a potential run for the presidency in 2012
Prologue: Political fictions : the lies of Sarah Palin -- pt. 1. Alaska. Wasilla -- Juneau -- pt. 2. America. Hail Mary -- Uncivil discourse -- Rogue -- pt. 3. Alaska. Cold comfort -- Unraveling -- pt. 4. America. The absence of fact -- Epilogue.
Includes bibliographical references (p. [429]-445) and index.
Keywords: Palin, Sarah, -- 1964-; Palin, Sarah, -- 1964- -- Ethics; Women governors -- Alaska -- Biography; Governors -- Alaska -- Biography; Vice-Presidential candidates -- United States -- Biography; Presidential candidates -- United States -- Biography; Deception -- Political aspects -- United States; Alaska -- Politics and government -- 1959-; United States -- Politics and government -- 2001-2009.; United States -- Politics and government -- 2009-